Sex Difference in Strength and Size Ratios between Reciprocal Muscle Groups in the Lower Leg - Akagi, R.; Tohdoh, Y.; Takahashi, H. (International Journal of Sports Medicine, 2013)
This study compared strength and size of reciprocal muscle groups in the lower leg between sexes. 20 young men and 14 young women volunteered as subjects. Joint torques developed during isometric maximal voluntary plantar flexion (TQPF) and dorsiflexion (TQDF) were measured using a dynamometer. Muscle volumes of plantar flexors (MVPF) and dorsiflexors (MVDF) were determined by magnetic resonance imaging. In each of the muscle groups, joint torque was significantly correlated with muscle volume in young men and women (r=0.610–0.848) and the y-intercept of the regression line between them was not significantly different from zero. Based on these observations, the dependencies of muscle strength ratio on muscle size ratio between the plantar flexors and dorsiflexors were investigated using joint torque and muscle volume. The correlations between the MVPF per MVDF and the TQPF per TQDF were significant both in young men (r=0.608) and women (r=0.773), suggesting that strength ratio is strongly affected by size ratio between the plantar flexors and dorsiflexors in young men and women.
Keywords: joint torque; muscle volume; plantar flexors; dorsiflexors